Do new labour activation policies work? A descriptive analysis of the German Hartz reforms - Jens Alber; Jan Paul Heisig (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2011)
The German Hartz reforms, introduced by the Red-Green coalition government in the years 2003 to 2005, form part of a broader pattern of European activation policies which have become known as new labour policies. The idea of these reforms was to reduce welfare dependency and to boost activity rates by making work pay, and by transforming the welfare state from a passive instrument of social protection to an enabling social investment that fosters universal labour force participation as the ultimate form of social inclusion. The German variety of these policies abolished earnings-related benefits to the long-term unemployed, partly fused the unemployment compensation scheme with the minimum income social assistance scheme and increased activating pressures on ablebodied people at working age by combining new sanctions with an extension of placement services. Based on a description of the relevant institutional changes, we show that means-tested benefits have become the major form of social transfer payments to the unemployed. The reforms also entailed a massive growth in German employment and especially in low-wage employment. As non-standard forms of employment proliferated, growing proportions of economically active people joined the ranks of the working poor by combining earnings from work with means-tested in-work benefits. Based on survey data from the German Socio-Economic Panel (GSOEP), we show that the working poor enjoy higher life satisfaction, social integration and civic engagement than the nonworking poor. However, these individual and social benefits of employment critically depend on pay levels and overall job quality, as our own analyses confirm for the case of men's life satisfaction. The welfare gains achieved by Germany's recent reforms may therefore be smaller than suggested by employment rates alone, because people near the poverty line are now more willing to make concessions and to accept job offers even if the jobs they get are of minor quality. – – Die von der rot-grünen Bundesregierung nach der Jahrtausendwende durchgesetzten Hartz-Reformen sind Teil eines allgemeinen Musters der Aktivierungspolitik, die von mehreren sozialdemokratischen Regierungen Europas unter dem Stichwort new labour betrieben wurde. Das Ziel dieser Reformpolitik war es, die Abhängigkeit von staatlichen Transferzahlungen zu mindern und das Beschäftigungsniveau zu steigern, indem Arbeit im Niedriglohnsektor mit Hilfe von Subventionen attraktiver gemacht und der Sozialstaat von einer reaktiven Instanz des sozialen Schutzes zu einem befähigenden Instrument sozialer Investition umgebaut wurde. Die deutsche Variante dieser Politik schaffte die einkommensbezogenen Leistungen für Langzeitarbeitslose ab, fusionierte die soziale Sicherung der Arbeitslosen teilweise mit der Sozialhilfe und erhöhte den Aktivierungsdruck auf die Leistungsempfänger durch eine Politik des Forderns und Förderns, die neue Sanktionsmöglichkeiten mit verbesserten Bildungs- und Vermittlungsdiensten verband. Auf der Grundlage einer Beschreibung der wichtigsten institutionellen Reformen zeigen wir, dass die an Bedürftigkeitstests gebundene Grundsicherung heute die bei weitem häufigste Transferzahlung für Arbeitslose darstellt. Das Beschäftigungsniveau ist seit den Reformen insbesondere im Niedriglohnsektor beträchtlich gestiegen. Da vor allem diverse Formen atypischer Beschäftigung zugenommen haben, zählt ein wachsender Teil der Erwerbstätigen zur Gruppe der arbeitenden Armen, die ihr Erwerbseinkommen mit Leistungen der Grundsicherung aufstocken. Auf der Basis von SOEP-Daten zeigen wir, dass die arbeitenden Armen nicht nur zufriedener, sondern auch in vielfältiger Weise besser sozial integriert sind als vergleichbare nicht arbeitende Arme. Wie wir am Beispiel der Lebenszufriedenheit von Männern zeigen, hängen die positiven Effekte der Erwerbstätigkeit allerdings entscheidend von der Entlohnung und anderen Aspekten der Arbeitsplatzqualität ab. Die Wohlfahrtsbilanz der Hartz-Reformen könnte deshalb ungünstiger ausfallen, als die Beschäftigungsentwicklung vermuten lässt, da Arbeitsuchende nun eher zu Konzessionen bereit sind und auch schlechtere Stellenangebote akzeptieren.
Keywords: I38; J68; 330; Minimum income support; unemployment compensation; labour market reforms; Hartz reform; activation policy; social inclusion; recommodification; working and non-working poor; Mindestsicherung; Arbeitslosenunterstützung; Arbeitsmarktreformen; Hartz-Reform; Aktivierungspolitik; soziale Inklusion und Teilhabe; Rekommodifizierung; arbeitende und nicht arbeitende Arme; Hartz-Reform; Aktivierende Sozialhilfe; Arbeitsmarktpolitik; Beschäftigungseffekt; Armut; Zufriedenheit; Deutschland